Periodic poling with a micrometer-range period in thin-film lithium niobate on insulator - Younesi, Mohammadreza; Geiss, Reinhard; Rajaee, Shakiba; Setzpfandt, Frank; Chen, Yen-Hung; Pertsch, Thomas (Journal of the Optical Society of America B-Optical Physics, 2021)
We present our experimental results on electric field poling of X-cut thin-film lithium niobate with poling periods of 1–4 µm. We used polarization contrast microscopy combined with digital image processing to study the impact of the experimental parameters of the poling process such as electric field strength, poling pulse duration, and layout of metal electrodes on the domain growth and quality of resulting poling patterns. High-quality results with excellent homogeneity of the domain pattern on large areas [i.e., 16 µm along the domain (z axis) and millimeter long domain gratings along the y axis with a period down to 1 µm] allow for the integration of numerous devices and structures.
CRIS-Team Scopus Importer:2023-04-20